Evaluation of tertiary treatment by fungi, enzymatic and photo-Fenton oxidation on the removal of phenols from a kraft pulp mill effluent: a comparative study - Justino, Celine (2019)
Pulp and paper mills generate pollutants associated to their efﬂuents depending upon the type of process, type of the wood materials, process technology applied, management practices, internal recirculation of the efﬂuent for recovery, the amount of water used in the industrial process and type of secondary treatment. This study is the ﬁrst that reports a simultaneous evaluation of the effects of tertiary treatments by fungi (Rhizopus oryzae and Pleurotus sajor caju), by enzyme (laccase) and by an oxidation process (photo-Fenton) on individual phenols (vanillin, guaiacol, phloroglucinol, vanillic acid and syringic acid) of a Eucalyptus globulus bleached kraft pulp and paper mill ﬁnal efﬂuent after secondary treatment (BKPME). The tertiary treatments were applied on BKPME samples and in BKPME samples supplemented with extra concentration of each phenol. Tertiary treatments by Rhizopus oryzae and photoFenton oxidation were able of complete removal (100%) of phenols on BKPME samples whereas P. sajor caju and laccase were able of 60–85% removal. On BKPME samples with added concentration of each phenol, photo-Fenton was the only treatment capable of total phenols removal (100%), which suggests a great potential for its application.